Comparison of the Legitimacy of Digital Gold Investment from the Perspective of Islamic Economic Law: A Normative Approach - Nurul Isna Faizatul Munna (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study aims to examine the comparison of digital gold investment practices on the DANA and Tring! By Pegadaian applications and the legitimacy of digital gold investment from the perspective of Sharia Economic Law. The approach used in this study is normative qualitative. The types of data used are primary and secondary data. Primary data was obtained using the observation method on both applications. Meanwhile, secondary data was obtained through literature study. The data analysis technique used descriptive analysis by grouping data, interpreting data, and providing an overall interpretation. This resulted in the finding that the digital gold investment mechanisms on the DANA and Tring! by Pegadaian applications both make it easy for people to invest in gold digitally through account creation, balance top-ups, purchases, price monitoring, and gold sales. DANA Emas offers a simpler process with disbursement generally in the form of balance, while Tring! by Pegadaian provides more diverse services through savings and gold installments as well as physical gold exchange. From the perspective of Sharia Economic Law, digital gold investment on both applications is deemed valid because it uses Sharia-compliant contracts, namely the sale and purchase contract (bai'), wadi'ah, and wakalah bil ujrah, as well as the murabahah contract for the gold installment service on Tring! by Pegadaian.